Bioinformatics analysis of electroacupuncture treatment for ischemic stroke: exploring transcriptional regulatory mechanisms mediated by super-enhancers - Wu, Chunxiao; Wang, Qizhang; Xu, Zhirui; Deng, Chuyu; Tang, Chunzhi (Frontiers in Neuroscience, 2025)
BackgroundIschemic stroke is a leading cause of disability and mortality, imposing substantial physical, emotional, and economic burdens on patients and society. This study aimed to explore the regulatory effects of super-enhancers (SEs) on gene expression in the context of ischemic stroke and their potential transcriptional regulatory mechanisms.MethodsSuper-enhancers were identified via H3K27ac chromatin immunoprecipitation sequencing (ChIP-seq) and ROSE software. RNA-sequencing (RNA-seq) was employed to screen for differentially expressed genes. A comparative analysis of ChIP-seq and RNA-seq data initially identified SE target genes, followed by further screening of key core differentially expressed SE target genes via the random forest method. The identified core SE target genes were initially validated through immunofluorescence and immunoblotting techniques. Additionally, potential core transcriptional regulatory circuits were preliminarily screened via the Coltron algorithm.ResultsWe identified SE-associated genes in the ischemic stroke model and electroacupuncture-treated groups, revealing 41 genes uniquely regulated by SEs in the electroacupuncture group compared with 367 in the model group. Enrichment analyses revealed that pathways involved in axon guidance, regulation of lipolysis in adipocytes and sphingolipid signaling pathway were significantly enriched in the SE target genes, suggesting that these pathways may be involved in the therapeutic effects of electroacupuncture. Notably, HDAC7 emerged as a key SE-driven gene; its expression was significantly reduced following electroacupuncture treatment, indicating its potential as a therapeutic target. Protein expression analyses confirmed elevated levels of HDAC7 in the model group, which were reduced by electroacupuncture intervention (p < 0.05). Furthermore, core transcriptional regulatory circuitries involving SOX8, FOXK1, and KLF13 were identified, highlighting their roles in the modulation of SE-mediated gene regulation by acupuncture in the ischemic stroke context.ConclusionOverall, our findings provide novel insights into the molecular mechanisms by which acupuncture may treat ischemic stroke, identifying key SE target genes and transcriptional circuits as promising targets for future therapeutic strategies. Further research is warranted to validate these findings in clinical settings and explore the translational potential of acupuncture in ischemic stroke treatment.